Bi2WO6/C-Dots/TiO2: A Novel Z-Scheme Photocatalyst for the Degradation of Fluoroquinolone Levofloxacin from Aqueous Medium - Shelja Sharma; Alex O. Ibhadon; M. Grazia Francesconi; Surinder Kumar Mehta; Sasikumar Elumalai; Sushil Kumar Kansal; Ahmad Umar; Sotirios Baskoutas (Nanomaterials, 2020)
Photocatalytic materials and semiconductors of appropriate structural and morphological architectures as well as energy band gaps are materials needed for mitigating current environmental problems, as these materials have the ability to exploit the full spectrum of solar light in several applications. Thus, constructing a Z-scheme heterojunction is an ideal approach to overcoming the limitations of a single component or traditional heterogeneous catalysts for the competent removal of organic chemicals present in wastewater, to mention just one of the areas of application. A Z-scheme catalyst possesses many attributes, including enhanced light-harvesting capacity, strong redox ability and different oxidation and reduction positions. In the present work, a novel ternary Z-scheme photocatalyst, i.e., Bi2WO6/C-dots/TiO2, has been prepared by a facile chemical wet technique. The prepared solar light-driven Z-scheme composite was characterized by many analytical and spectroscopic practices, including powder X-ray diffraction (XRD), field emission scanning electron microscopy (FE-SEM), N2 adsorption–desorption isotherm, Fourier-transform infrared spectroscopy (FT-IR), photoluminescence (PL) and UV-vis diffuse reflectance spectroscopy (DRS). The photocatalytic activity of the Bi2WO6/C-dots/TiO2 composite was evaluated by studying the degradation of fluoroquinolone drug, levofloxacin under solar light irradiation. Almost complete (99%) decomposition of the levofloxacin drug was observed in 90 min of sunlight irradiation. The effect of catalyst loading, initial substrate concentration and pH of the reaction was also optimized. The photocatalytic activity of the prepared catalyst was also compared with that of bare Bi2WO6, TiO2 and TiO2/C-dots under optimized conditions. Scavenger radical trap studies and terephthalic acid (TPA) fluorescence technique were done to understand the role of the photo-induced active radical ions that witnessed the decomposition of levofloxacin. Based on these studies, the plausible degradation trail of levofloxacin was proposed and was further supported by LC-MS analysis.